Research Progress on Enzymatic Preparation and Functional Properties of Bioactive Peptides in Hairtail - Yuanyuan WU; Kewei ZHENG; Wenzhu LI; Cheng LI; Xiaojun YAN; Qingbao MA; Wei JIANG (Shipin gongye ke-ji)
Hairtail is a significant economic fish species in China, rich in protein and other nutrients, making it an excellent source of bioactive peptides. This review provides the enzymatic hydrolysis processes and auxiliary methods used for preparing hairtail bioactive peptides. The antioxidative activity of enzymatic hydrolysates is extensively studied, with alkaline protease and papain being the most commonly used enzymes. However, research on the specific peptide sequences responsible for bioactivity and their underlying mechanisms remains limited. This review discusses the current state of research on the bioactivities of hairtail peptides, including antioxidative, antihypertensive, antibacterial, antidiabetic, antifatigue, anti-anemia, and growth regulation activities. The evaluation methods, key influencing factors, and effectiveness of these bioactivities are summarized. Most existing studies on hairtail bioactive peptides focus on in vitro activities, highlighting the need for in vivo activity verification and molecular-level research as important future directions. This review also addresses current issues in hairtail bioactive peptide research, providing insights for their development and application. The simple preparation process and diverse bioactivity of hairtail-derived bioactive peptides present broad application prospects in the food industry, health products, and pharmaceuticals.